(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article provides a comprehensive literature review on the clinical description and treatment approaches for Crimean-Congo hemorrhagic fever (CCHF). The paper summarizes epidemiological data, clinical features, and therapeutic interventions described in contemporary research. It highlights that CCHF remains a serious zoonotic infection with a high fatality rate, predominantly affecting regions of Asia, Africa, and Eastern Europe. The analysis of recent studies reveals that early administration of ribavirin and intensive supportive therapy can reduce mortality, although their efficacy varies. Current investigations focus on the development of new antiviral agents and immunotherapeutic options. The review emphasizes the need for early diagnosis, adequate supportive management, and strict infection control to improve clinical outcomes and prevent nosocomial transmission.